“You can push these conversations, but don’t push your patient away”: healthcare learner perspectives on virtual simulation games as an educational approach to address vaccine hesitancy - Emily J. Doucette; Margaret Pateman; Margaret Pateman; Madison M. Fullerton; Madison M. Fullerton; Alyssa Lip; Sherilyn K. D. Houle; James D. Kellner; James D. Kellner; Jenine Leal; Jenine Leal; Jenine Leal; et al. (Frontiers in Public Health, 2024)
BackgroundVaccine hesitancy is a significant threat to public health. Healthcare providers (HCPs) can address hesitancy during routine patient conversations; however, few multidisciplinary education tools exist for HCPs to learn to engage in vaccine discussion especially considering new vaccine technologies such as mRNA vaccines. The objectives of this study were to explore HCP learners’ experiences with COVID-19 vaccine communication, and qualitatively evaluate an online learning module composed of virtual simulation games (VSGs) which utilize the PrOTCT Framework for HCP vaccine communication.MethodsThree virtual focus groups were conducted from December 2022 to January 2023 with Canadian healthcare learners in nursing (N = 6), pharmacy (N = 9), and medicine (N = 7) who participated in a larger study measuring the effectiveness of the VSGs. Using a pragmatic approach, a qualitative thematic analysis was conducted using NVivo to identify themes and subthemes.ResultsA total of 22 HCP learners participated in this study and three key themes were identified. Across all three disciplines, participants expressed that (1) their prior education lacked training on how to hold vaccine conversations, resulting in uncomfortable personal experiences with patients; (2) the VSGs increased their confidence in holding vaccine conversations by providing novel tools and skills; and (3) participants also provided feedback to improve the VSGs which was implemented and supported the dissemination to all HCP professions.ConclusionAlthough HCPs are a trusted source of vaccine information, participants in this study felt they received little training on how to engage in challenging conversations regarding COVID-19 vaccines. The introduction of the PrOTCT Framework and presumptive statements provided novel strategies for HCP to initiate vaccine conversations, especially considering new vaccine technologies and participants appreciated the emphasis on coping strategies and resilience. It is essential that HCP are provided both opportunities to practice managing these conversations, and tools and skills to succeed at an early point in their careers to prepare them for future roles in vaccine advocacy, delivery, and promotion.